Lingkungan Hidup Manusiawi Ahimsa dan Transformasi Budaya - Jacobus Tarigan (Respons: Jurnal Etika Sosial, 2008)
Men and earth are inseparable unity. The is a dialectical relationship between them. There is no man without earth. Man is not a lord to his environment. The domination of man upon earth is denied. Man is required to give a friendly and respectful attitude to environment. Man is using the environment and maintaining it at the same time. The principle of justice penetrates the relationship old man with his environment. The destruction of the environment is a concern for everybody, institutions and states. The concern is not enough to be shown by conducting a lot of discussion and reflections, but it must be expressed in very real actions: looking at the problem, considering the problem and making solution as well as takin it into action. The philosophical-ethical reflection and critical-ethical evaluation must be based on experience.